2006
DOI: 10.1103/physrevc.74.034332
|View full text |Cite
|
Sign up to set email alerts
|

Average ground-state energy of finite Fermi systems

Abstract: Semiclassical theories such as the Thomas-Fermi and Wigner-Kirkwood methods give a good description of the smooth average part of the total energy of a Fermi gas in some external potential when the chemical potential is varied. However, in systems with a fixed number of particles N , these methods overbind the actual average of the quantum energy as N is varied. We describe a theory that accounts for this effect. Numerical illustrations are discussed for fermions trapped in a harmonic oscillator potential and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 30 publications
(60 reference statements)
1
32
0
Order By: Relevance
“…In particular, the average is positive for a fixed shape, while it is negative in self-bound systems. Such a bias toward negative energies of the fluctuating part in self-bound systems is clearly observed in realistic calculations [5]. In the bottom part of Fig.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In particular, the average is positive for a fixed shape, while it is negative in self-bound systems. Such a bias toward negative energies of the fluctuating part in self-bound systems is clearly observed in realistic calculations [5]. In the bottom part of Fig.…”
Section: Introductionsupporting
confidence: 52%
“…Recently, an explicit description for this effect was given. It was found that the contribution of the fluctuating part to the average of the energy is given by [5] …”
Section: General Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The semiclassical Wigner-Kirkwood (WK) approach [18][19][20][21][22][23][24][25], on the other hand, makes no explicit reference to the single-particle spectrum, and achieves an accurate averaging of the given one-body Hamiltonian. Thus, the WK approach is a good alternative to the conventional Strutinsky smoothing scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Using semiclassical POT arguments, the difference between energy and particle-number averaging was understood [41,42] as a symmetry correction which becomes especially significant for spherical nuclear shapes (particularly in the harmonic oscillator model). Smaller discrepancies for the deformed Fermi systems in the resulting shell-correction energies persist, however, as discussed in [41,42,43]. This point is thus still an object of current debate.…”
Section: 7)mentioning
confidence: 99%